FREQUENCY OF LOW APGAR SCORE IN NEWBORNS WITH ABNORMAL CTG (The Research of Medical Science Review, 2025)
Background: Cardiotocography (CTG) is a widely used tool for fetal monitoring during labor. Abnormal CTG patterns have been associated with adverse neonatal outcomes, including low Apgar scores. The Apgar score is very rapid assessment of the newborn’s health instantly after birth, with lower scores indicating potential perinatal distress and the need for medical intervention. Early identification of neonates at danger of low Apgar scores is crucial for improving perinatal outcomes. Aim: This article intended to regulate frequency of low Apgar scores in newborns with abnormal CTG findings and assess the predictive value of abnormal CTG in identifying neonates at risk of poor perinatal outcomes. Methods: A cross-sectional study was conducted at the Department of Gynecology and Obstetrics, Bilawal Medical College, CDF Hospital, Hyderabad, from August 2024 to January 2025. The study included 149 pregnant women with abnormal CTG findings, selected through the nonprobability consecutive sampling technique. Data were collected on maternal demographics, gestational age, mode of delivery, and neonatal Apgar scores at 1 and 5 minutes. The positive predictive value (PPV) of abnormal CTG in predicting low Apgar scores was calculated, literally having standard deviations and confidence intervals. Statistical analysis was performed by means of SPSS software, with the substantial level set at p<0.05. Results: Out of 149 neonates with abnormal CTG findings, 43 (28.9%) had the low Apgar score (<7) at 1 minute, while 19 (12.8%) had a persistently low Apgar score at 5 minutes. The positive predictive value of abnormal CTG for identifying neonates with a low 1-minute Apgar score was 28.9%, with a standard deviation of ±3.6. Emergency cesarean section was performed in 67 cases (45.0%) due to abnormal CTG patterns, and 21 neonates (14.1%) required neonatal intensive care unit (NICU) admission. A significant association was found between persistently low Apgar scores and emergency cesarean sections (p<0.05). Conclusion: Abnormal CTG findings were associated with a substantial proportion of neonates having low Apgar scores, indicating fetal distress. However, the positive predictive value of abnormal CTG for predicting poor neonatal outcomes remained moderate. While CTG is a valuable tool for fetal surveillance, its predictive limitations necessitate clinical correlation and additional fetal monitoring methods for accurate decision-making.